Rancang Bangun Alat Simulasi Latihan Menembak Berbasis Arduino Uno - Fiki S. Saro; Sherwin R.U.A. Sompie; Elia K. Allo (Universitas Sam Ratulangi, 2018)
Abstract — This final project is designed to design an arduino uno-based arduous training simulation tool that can make it easier to know the score of shots displayed on the smartphone. Shooting scores will be displayed if the photodiode sensor gets or receives light from the laser pointer designed on the weapon, the scores received will be displayed on the seven segment as well as the display on existing applications on the smartphone. the data display on the smartphone has 10 shots data. Of the 10 shot data summed into a total score that can be viewed on smartphone applications. The data displayed on the smartphone can be sent via Bluetooth communication after being processed by Arduino uno. This shooting simulation tool can make it easier for training and also reduce the budget for shooting practice. Keywords — Arduino; Bluetooth; Photodiode; Shooting; Simulation; Smartphone Abstrak — Tugas akhir ini buat untuk merancang alat simulasi latihan menembak berbasis arduino uno yang dapat mempermudah dalam mengetahui skor tembakan yang ditampilkan pada smartphone. Skor tembakan akan ditampilkan apabila pada sensor photodiode mendapatakan atau menerima cahaya dari laser pointer yang didesain pada senjata, skor yang diterima akan ditampilakan pada seven segment serta tampilan pada aplikasi yang ada di smartphone. tampilan data pada smartphone memiliki 10 data tembakan. Dari 10 data tembakan dijumlahkan menjadi skor total yang boleh dilihat pada aplikasi smartphone. Data yang ditampilkan pada smartphone dapat dikirim melalui komunikasi Bluetooth setelah diproses oleh Arduino uno. Dengan adanya alat simulasi menembak ini dapat mempermudah untuk pelatihan dan juga memperkecil anggaran untuk latihan menembak.Kata kunci — Arduino; Bluetooth; Menembak; Photodiode; Simulasi; Smartpone